Kemampuan Komunikasi Matematis Siswa dalam Menyelesaikan Soal Teorema Pythagoras ditinjau dari Minat Belajar - Cahya Ningrum Ma'idah Putri; Sri Subarinah; Tabita Wahyu Triutami (Griya Journal of Mathematics Education and Application, 2026)
Mathematical communication ability is the student's ability to convey mathematical ideas through writing, symbols, and visual representations. Learning interest is one of the factors that encourages students to be more active in learning and more confident in expressing mathematical ideas. This study aims to describe students' mathematical communication abilities in solving Pythagorean Theorem problems in terms of learning interest. This research uses a qualitative descriptive approach and was conducted in class VIII of SMP Negeri 7 Mataram in the 2025/2026 academic year. The subjects of this study were 42 students, consisting of 11 students with high learning interest, 18 students with moderate learning interest, and 13 students with low learning interest. Furthermore, 8 students were selected for interviews, consisting of 3 students with high interest, 3 with moderate interest, and 2 with low interest. Data collection techniques included questionnaires, tests, and interviews. Data analysis was performed through data reduction, data presentation, and drawing conclusions. The results showed that students' mathematical communication abilities differ at each level of learning interest. Students with high interest tend to be better at expressing ideas and using symbols; students with moderate interest are fairly good but still have difficulty explaining the solution steps; whereas students with low interest have difficulty expressing ideas and explaining the problem-solving process. Thus, learning interest is not always directly proportional to students' mathematical communication abilities.